Vent Control as a Means of Enhancing Airbag Performance - Richard E. Zimmermann (Shock and Vibration)
Typical automotive airbag systems have a fixed area vent for exiting gasses. The US Army Cockpit Airbag System (CABS) is unvented to prolong the period during which the system can provide occupant protection during extended helicopter crash scenarios. In each application, system performance may be enhanced by providing a controlled vent area. This paper describes work conducted under a Phase I SBIR program sponsored by the NASA Langley Research Center. The work was focused on eventual inflatable restraint system applications in general aviation aircraft, and showed that appropriate vent control offers many enhancements. Two series of tests conducted during Phase I showed that inflatable restraint system size and weight can be reduced without degrading performance, injury potential in an out of position situation (OOPS) deployment can be reduced, and peak bag pressures can be reduced (at any temperature) during normal operation.